2019
DOI: 10.46660/ijeeg.vol10.iss1.2019.223
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Plan Behavior and Norm Activation Model to Understand Individual Energy Conservation Behavior in Karachi, Pakistan

Abstract: The environmental problems are considered as a serious threat to the future of humanity. The adoption ofsustainable behaviors is considered a necessary step to deal with the environmental challenges. Energy conservationbehavior is an environment friendly behavior that has been promoted in many societies. Researchers have been studyingthe determinants of energy conservation behavior for many years, in western countries. However, energy conservationbehavior of individuals in the house has not received attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Due to their ignorance, families, colleagues, friends, and important people cannot remind, encourage, or invite each other to participate in the program. This is in line with previous studies, which concluded that subjective norms do not affect willingness to pay to reduce noise pollution in land transportation [52], the intention to reduce car travel, energy conservation behavior, and the intention to purchase green products [49,51,63]. However, several studies provided different results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to their ignorance, families, colleagues, friends, and important people cannot remind, encourage, or invite each other to participate in the program. This is in line with previous studies, which concluded that subjective norms do not affect willingness to pay to reduce noise pollution in land transportation [52], the intention to reduce car travel, energy conservation behavior, and the intention to purchase green products [49,51,63]. However, several studies provided different results.…”
Section: Discussionsupporting
confidence: 91%
“…NAM highlights the importance of personal norms for predicting individual behavior. Several studies have expanded the TPB model by integrating NAM [36,[49][50][51]. VBNT combines the components of values and norms from NAM and the New Environmental Paradigm (NEP), including common beliefs and concerns about the environment and the need for action to address problems [44].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in global energy consumption has led to a serious concern about the depletion of natural resources and a number of environmental issues (Liu, Wang, Wei, Chi, Ma & Jian, 2020, Dumciuviene, Cibinskiene & Andrijauskiene, 2019. Global warming, depletion of natural resources, water and air pollution have got the attention of academics and policymakers due to their hazardous effect on the quality of life on the planet (Rasool, Zuberi, Siddiqui & Madni, 2019). Among the various sources of energy, electrical energy is the most widely used source of energy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yue et Global Management Sciences Review (GMSR) al. (2019), Abrahamse and Steg (2009), Dumciuviene et al (2019), Sardianou (2007), Wang et al (2011), Rasool et al (2019) emphasized the role households psychological and socio-demographic attributes in the consumption and conservation of energy in the developing countries. The theory of planned behavior (TPB) proposed by Ajzen (1991) claims that behavioral intension mediates the relation between different psychological, socio-demographic variables and energy conservation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation